The Effects of Contextual Factors, Self-Efficacy and Motivation on Learners’ Adaptability to Blended Learning in College English: A Structural Equation Modeling Approach - Yang, Shuhan; Pu, Ruihui (Frontiers in Psychology, 2022)
Abstract Objective: Few research efforts have quantitatively investigated the relevant affecting factors on students’ adaptability to explain the ineffectiveness of blended learning mode in College English. Based on social cognitive theory and previous studies concerning adaptability, this study attempted to propose a model and examine the involved correlations among contextual factors, self-efficacy, motivation and adaptability of non-English majored learners of College English with blended learning mode. Methods: The survey was conducted among 900 non-English majored learners selected with stratified random sampling method and structural equation modeling (SEM) was used to analyze the data. Results: (1) The non-English majored learners’ adaptability in College English with blended model was at a low level (mean=2.26); (2) The structural model had an overall good fit to the data: x2/df=2.496, RMESA=0.050, GFI=0.956, AGFI=0.936, NFI=0.968, RFI=0.959, IFI=0.980, TLI=0.975, CFI=0.980; (3) The path coefficients presented in the final model indicated that adaptability was positively impacted by contextual factors, self-efficacy and motivation (p < 0.001); (4) Separate mediating effect and chain mediating effect existed between contextual factors and adaptability through self-efficacy and motivation (p < 0.01). The separate indirect effect was 0.277 and 0.157 respectively, and the chain mediating effect was 0.059. Implications: These findings not only extended the studies on adaptability, but shed light on the mechanism of promoting non-English majored learners’ adaptability and bringing them positive emotional experience in blended learning environment, which would be insightful for the successful implementation of blended learning in knowledge industry.